Pengaruh Intensitas Modal, Struktur Modal, Perputaran Modal Kerja Terhadap Kinerja Keuangan Dimoderasi Komisaris Independen - Nathasya Mutiara Cahyani Kurniawan; Basuki Toto Rahmanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to analyze the effect of Capital Intensity, capital structure, working capital turnover on financial performance moderated by independent commissioners. Capital Intensity was measured using the Capital Intensity ratio, capital structure was measured using the Debt To Equity Ratio, working capital turnover was measured using working of capital turnover (WCTO), financial performance was measured using Return On Assets. The population used in this study uses companies listed in the food and beverage sektor that are listed on the IDX in 2016-2020. The technique used in determining the sample is purposive sampling with a total of 105 observations. The analytical method used in this research is Moderate Regression Analysis (MRA). The hypothesis is accepted if the probability value is 0.05. The results showed that Capital Intensity, capital structure and working capital turnover had no effect on financial performance, independent commissioners did not moderate the effect of Capital Intensity, capital structure and working capital turnover on financial performance.